If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5a + 4) + 1 = 2 + -1(5a + -1) Reorder the terms: -1(4 + 5a) + 1 = 2 + -1(5a + -1) (4 * -1 + 5a * -1) + 1 = 2 + -1(5a + -1) (-4 + -5a) + 1 = 2 + -1(5a + -1) Reorder the terms: -4 + 1 + -5a = 2 + -1(5a + -1) Combine like terms: -4 + 1 = -3 -3 + -5a = 2 + -1(5a + -1) Reorder the terms: -3 + -5a = 2 + -1(-1 + 5a) -3 + -5a = 2 + (-1 * -1 + 5a * -1) -3 + -5a = 2 + (1 + -5a) Combine like terms: 2 + 1 = 3 -3 + -5a = 3 + -5a Add '5a' to each side of the equation. -3 + -5a + 5a = 3 + -5a + 5a Combine like terms: -5a + 5a = 0 -3 + 0 = 3 + -5a + 5a -3 = 3 + -5a + 5a Combine like terms: -5a + 5a = 0 -3 = 3 + 0 -3 = 3 Solving -3 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y | | 61-4x=10+19 | | m/-4=-2.27 | | -5(4a-5)=2(3-10a)+19 | | -52-5x=8-8x |